Tratado de Derecho agrario, Esther Muñiz Espada, Pablo Amat Llombart (directores), Wolters Kluwer España, S.A., Madrid 2017, ss. 972. - Budzinowski, Roman; Różański, Krzysztof (Przegląd Prawa Rolnego, 2019)
Review